Back to the Future: Restoring Northern Drained Forested Peatlands for Climate Change Mitigation - Escobar, Daniel; Belyazid, Salim; Manzoni, Stefano (Frontiers in Environmental Science, 2022)
Draining peatlands in the northern hemisphere have turned their soils from carbon sink to substantial sources of green-house gases (GHG). To reverse this trend, rewetting has been proposed as a climate change mitigation strategy. We performed a literature review to assess the empirical evidence supporting the hypothesis that rewetting of drained forested peatlands can turn them back into carbon sinks. We also used causal loop diagrams (CLDs) to synthetized the current knowledge of how water table management affects GHG emissions in organic soils. We found an increasing number of studies comparing GHG emissions from rewetted peatlands with forested or pristine peatlands in the last decade. However, comparative field studies usually report relatively short timeseries of data for young rewetted systems for short term periods (e.g. 3 years of measurements and around 10 year after rewetting). Empirical evidence shows that rewetting leads to lower GHG emissions from soils, however reports of carbon sinks in rewetted systems are scarce in the reviewed literature. Moreover, CH4 emissions in rewetted peatlands tend to be higher than in pristine peatlands. Long-term water table changes lead to a cascade of effects in different processes related to GHG emissions. Water table affects litterfall quantity, litterfall quality, organic matter breakdown rates, carbon and nitrogen mineralization pathways and rates, as well as gas transport mechanisms. Finally, we conceptualized three phases of GHG emission following the rewetting of previously drained peatlands, concluding that while short-term gains in the GHG balance can be minimal, the long-term potential of restoring drained peatlands through rewetting remains promising.